A novel method for repeated cerebrospinal fluid sampling and long-term monitoring of intracranial pressure in rats - Hao, Guangshan; Zhang, Qia; Chen, Weiyu; Mo, Jun (Frontiers in Neuroscience, 2023)
Cannulation implantation into the cisterna magna is an important procedure in cerebrospinal fluid (CSF) sampling and intracranial pressure (ICP) monitoring. The disadvantages of existing techniques include the risk of brain damage, compromised muscle mobility, and the complexity of the procedures. In the present study, the authors describe a modified, simple, and reliable procedure for long-term cannulation implantation into the cisterna magna in rats. The device consists of four parts: the puncture segment, the connection segment, the fixing segment, and the external segment. Intraoperative ICP monitoring and post-operative computed tomography (CT) scans were performed, which confirmed the accuracy and safety of this method. There were no limitations on the daily activities of the rats when long-term drainage was carried out for 1 week. This new technique offers an improved method of cannulation and will be a potentially useful method for CSF sampling and ICP monitoring in neuroscience research.